BioActivities of Coturnix japonica (quail) egg yolk and albumen against physiological stress - Oladipo, Gideon O. (Food Sci Nutr, 2016)
Cold and immobilization stressors can generate oxidative stress as well as skeletal muscle fatigue. Free radicals cause oxidative degradation of lipids, proteins, nucleic acids, and carbohydrates molecules thereby compromising cell integrity and function. Coturnix japonica (quail) egg had been described as being very functional biochemically, due to the essential biomolecules it contains in very regulated quantity. This study was designed to evaluate the in vitro antioxidant activity of extracts of quail egg yolk and the albumen. The assessment of the antioxidant potentials was typified using the total antioxidant capacity, and ABTS, DPPH (1‐diphenyl‐2‐picrylhydrazyl) and hydroxyl radicals scavenging activities. Others are reducing power, metal chelating and lipid peroxidation inhibition activities. The antistress activities of quail egg yolk and albumen were evaluated on hepatopathic enzymes as well as endogenous antioxidant enzymes. The total antioxidant activities of the yolk extract (YE) and the albumen extracts (AE) were, respectively, 186.57 ± 6.441 mg/g and 172 ± 10.690 mg/g AAE (Ascorbic Acid Equivalent). The YE exhibited significant, potent and appreciable antioxidant activities than AE in a concentration‐dependent manner. The study confirmed that quail egg yolk contained highly antioxidative bioactive compounds not present in albumen, contributing to its (yolk) overall antioxidant and anti‐inflammatory (antistress) properties, thus necessitating their (albumen and yolk) beneficial effects in the management of oxidative and inflammatory conditions.